The Analysis of Fator Which Affect CPO Export Volume at PT. Astra Agro Lestari, Tbk (Study at: Amin Jaya Village, Kumai Subdistrict, Kotawaringin Barat District, Central Borneo) - Iskandar, Bryan Iskandar; Salim, Ubud (Jurnal Ilmiah Mahasiswa FEB, 2016)
Palm oil industry is one of important industries in Indonesia because it provide export earnings and provide job opportunity for Indonesian. The main product of palm oil industry is crude palm oil (CPO). High demand of CPO either in domestic or international cause CPO has high economic value. One of many palm oil industries in Indonesia is PT. Astra Agro Lestari, Tbk. Beside to provide domestic CPO need, CPO product of PT. Astra Agro Lestari was also sold abroad toward China, Vietnam and Malaysia. But CPO export volume of PT. Astra Agro Lestari continue to decrease due to the high of CPO export tax. Beside affected by CPO export tax, volume of CPO export by PT. Astra Agro Lestari was also affected by CPO domestic price, CPO export price and CPO production. This research aim to determine the effect of CPO export tax, CPO domestic price, CPO export price and CPO production toward volume of CPO export at PT. Astra Agro Lestari. Result of this research showed that CPO export tax and CPO domestic price were significant toward volume of CPO export at PT. Astra Agro Lestari whereas CPO export price and CPO production was not significant. CPO expot tax and CPO domestic price both had negatif effect toward volume of CPO export. The increasing of CPO export tax and CPO domestic price decreased volume of CPO export at PT. Astra Agro Lestari. Â  Keyword: CPO Export Tax, CPO Domestic Price, CPO Export Price, CPO Production, CPO Export Volume.